Credulity rather than general trust may increase vulnerability to fraud in older adults: a moderated mediation model. Issue 2 (15th March 2019) - Shao, Jingjin; Du, Weiping; Lin, Tian; Li, Xiying; Li, Jiamei; Lei, Huijie
ABSTRACT: The present study aimed to clarify whether it is credulity or general trust that specifically affects vulnerability to fraud, as well as investigating the mediating role of susceptibility to persuasion and the moderating role of greed in this relationship. 254 Chinese older adults completed measures of credulity, general trust, susceptibility to persuasion, greed, and vulnerability to fraud. The results showed that credulity, but not general trust, was positively correlated with vulnerability to fraud, after controlling for demographic covariates. Susceptibility to persuasion partially mediated the effect of credulity on vulnerability to fraud. In addition, this mediating effect of susceptibility to persuasion was only significant in older adults with higher levels of greed. Our findings suggest that credulity, rather than general trust, is a risk factor in vulnerability to fraud among older adults, and may inform the development of supportive interventions to reduce this population's risk of falling victim to fraud.